STIGMATA OF EDUCATORS IN FRONT OF LEARNING DIFFICULTIES - PART I (Fiep Bulletin - online, 2016)
Students from low-income families have to overcome a difficult social barrier: one that puts them as intended for school failure, then begins the fight against stigma of all educators. Education is a process that requires a diverse set of knowledge and is the school's role to offer it to those who have no chance in the house. In this sense, we point as strategies decisive rapprochement between teaching staff of schools and representatives of the families, continuing education of teachers and the promotion of attitudes that sensitize students to knowledge. With scrapped education and unprepared teachers, many find alternative channels in the diversity needed to teach in the original form in Hebrew grow fruit etc .. It is impossible to find at home and at school referrals from people with a good accumulation of cultural capital which leads to search in other instances. The purpose of this is to educate the teacher of their knowledge through their professional competence, their attitudes and expectations about learning difficulties and the future of the student. Proposes that educators analysis of the context: immediate environmental conditions in which occurs the teaching-learning process (number of students specific circumstances in which it has the task, etc.); and mediate conditions (related linguistic, cultural, etc. the social and cultural group of student origin), with the psycho-pedagogical assessment.
Keywords: Learning; Difficulties; Pedagogy.